Political Discourse Analysis: Conceptual and analytical tools for the critical study of educational policies in times of global reform - Diego Palacios Díaz; Felipe Hidalgo Kawada; Rodrigo Cornejo Chávez; Noemí Suárez Monzón (Arizona State University, 2019)
In the context of a global educational reform movement, the principles and policies of the New Public Management (NPM) have become hegemonic to address the educational change in different countries of the world. Despite the critics received, there is a widespread perception that NPM programs are the most suitable to solve the problems that urge contemporary educational systems, which explains the massive adoption of their guidelines in different contexts. Recognizing that discursive and ideational aspects play an important role in this positioning, in this article we offer a set of conceptual and analytical tools to read critically educational policies in times of global reform. To fulfill this purpose, we examine the Norman Fairclough's Critical Discourse Analysis (CDA) approach and we link it with the Political Analysis of Discourse (PDA), a complementary analytical model to the CDA that distinguishes the specificities of the genre of public policies. Subsequently, and through an analytical exercise, we deployed a methodological - practical sequence for critical reading of texts and discourses of educational policy. Finally, we value the conceptual and analytical tools and emphasize on the need to integrate complaints and calls of hope through critical study of the discursive aspects of educational policy.